Analysis of Risk Factors of Stunting in Toddlers - Atikah Adyas; Sri Rejeki Wuwuh Handayani; Achmad Djamil; Ai Kustiani; Nathasa Khalida Dalimunthe (Jurnal Kesehatan, 2023)
Stunting is a childhood condition that experiences growth disorders characterized by a child's height that is not appropriate for their age and results from chronic nutritional problems. This study analyses the risk factors for stunting in West Tulang Bawang Regency. This study was a cross-sectional study. Data were collected through self-administered questionnaires from 265 mothers of children under five in three West Tulang Bawang Regency districts. This research used multivariate logistic regression to determine risk factors for stunting. The study assessed that 10.9% of their children were stunted. Nearly half of the mothers had low education (48.7%), and most did not work (79.6%). As many as 94.3% of mothers said they had a protected source of drinking water, while around 23.4% did not have sewerage. Most of the respondent's energy, fat, and carbohydrate adequacy level was classified as insufficient, and most children did not suffer from infectious diseases. The results of the correlation test showed that sewerage (AOR=4.309; p-value=0.000) was correlated with the occurrence of stunting, while a history of measles (AOR=3.482; p-value=0.150), energy adequacy level (AOR=2.691; p-value=0.057), birth order (AOR=2.949; p-value=0.050) not significantly correlated to stunting but had a high risk of stunting. Multivariate test results showed that no sewerage in families had a risk of about 4.192 times the occurrence of stunting in children compared to the presence of sewerage in West Tulang Bawang Regency.